(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article discusses the theoretical and methodological foundations of developing students’ geometric understanding. It analyzes the role of visualization, practical activities, interactive methods, and modern pedagogical technologies in forming geometric concepts. The issues of developing spatial thinking and organizing students’ independent and creative activities are also considered.